Protests and perceptions - Shannon Campbell (Communicare)
Protests and Perceptions: The Framing of the Modern Protester considers the role of the modern mass media in creating and perpetuating simplified images of newsworthy events and people. Specifically, an in-depth analysis of New York Times_and Washington Post coverage of the Summit of the Americas held from April 20, 2001 to April 22, 2001 in Quebec, Canada, provides examples of media framing of both Summit participants and protesters. The analysis shows that newspaper reports on the debate are presented through a pro-capitalist framework, which influences readers' perception of those who oppose globalization and free trade.